Utilization of Wokwi Technology as a Modern Electronics Learning Media - Darmaji, Darmaji; Jamlan, Muain; Nkweke, Obinna C; Boglou, A. K.; Baharin, Zain Hazmi Zain (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to develop Wokwi simulation-based teaching materials using the 4D model (Define, Design, Develop, Disseminate) to improve the understanding and science process skills of physics education students. Methodology: The Define stage identifies learning needs, while the Design stage designs interactive and easy-to-use teaching materials. In the Develop stage, the prototype is tested to assess the effectiveness of the simulation, resulting in a significant increase in students' understanding of basic concepts. This study involved 50 5th semester students at Jambi University, using questionnaires and observation sheets as instruments. Main Findings: The results of the analysis showed that the majority of students had science process skills in the